High cervical transmasseteric anteroparotid approach for mandibular condylectomy. Issue 3 (May 2021) - Okuda, Satoshi; Ono, Shigehiro; Tada, Misato; Ishida, Fumi; Uetsuki, Ryo; Takechi, Masaaki
Abstract: Giant cell granulomas are a type of giant cell lesions and classified as follows: central giant cell granulomas occurring in the mandible and peripheral giant cell granulomas occurring in the gingiva. Central giant cell granulomas are less frequent than peripheral giant cell granulomas, and it rarely occurs in the mandibular condyle. Mandibular condylectomy is a widely used treatment strategy for lesions in the mandibular condylar region. A commonly indicated treated for mandibular condylectomy is the preauricular approach or the Al-Kayat Bramley method; however, we used the high cervical transmasseteric anteroparotid (HC-TMAP) approach. In recent years, the use of this approach has been reported for open reduction and internal fixation for mandibular condylar fracture cases. In this case report, we describe a technique using the high cervical transmasseteric anteroparotid approach for resecting a mandibular condyle in which a central giant cell granuloma had developed.